A meta-analytic evaluation of the reliability of work-family and family-work conflict scales - Lawrence Ejike Ugwu; Erhabor Sunday Idemudia (Scientific Reports)
Abstract In occupational psychology, measuring the interplay between work and family roles is crucial. The Work-family conflict (WFC) and Family-Work Conflict (FWC) scales are indispensable tools in this endeavour. However, their reliability across diverse geographical locations and work settings, particularly during the global pandemic, requires thorough examination. This meta-analysis evaluates the reliability generalisation of WFC and FWC scales across different studies. Registered with PROSPERO (ID: CRD42024509030), we systematically searched four major databases: EBSCOhost, Web of Science, Scopus, and ScienceDirect, yielding 506 potential studies. After deduplication and screening, 44 studies published between 2000 and 2024 were selected. These studies analysed reliability coefficients (Cronbach’s alpha) and the impact of geographical location, work setting, and events like the COVID-19 pandemic on scale reliability. The analysis showed high reliability for both scales, with a pooled Cronbach’s alpha of 0.91 (95% CI [0.87, 0.95]) indicating strong internal consistency. Test-retest reliability was also high, with a pooled estimate of 0.89 (95% CI: [0.84, 0.93]). Subgroup analyses revealed minimal variability in reliability across sectors, regions, and the pandemic period, with no heterogeneity (I2 = 0.0%), suggesting the scales’ broad applicability. The WFC and FWC scales demonstrate high reliability across various global contexts, underscoring their value in occupational psychology. Their adaptability to different cultural and work scenarios, including during the COVID-19 pandemic, highlights their potential for widespread use. The uniform reliability across studies emphasises their effectiveness in capturing work-family dynamics, supporting their generalizability and relevance for cultural adaptation.